Spreading News in 1904. The Media Coverage of Nikolay Bobrikov's Shooting - Oiva Mila; Nivala Asko; Salmi Hannu; Latva Otto; Jalava Marja; Keck Jana; Martínez Domínguez Laura; Parker James (Taylor and Francis, 2022)
The assassination of Nikolay Bobrikov, the Governor-General of Finland, on 16 June 1904 was a turning point in Finnish history. It was reported in hundreds, if not thousands, of newspapers worldwide. This article follows the spread of that news, particularly its spread over the first week after the assassination. The study draws on the digital newspaper repositories in Australia, Austria, Denmark, Finland, France, Germany, Mexico, Sweden, the Netherlands and the United States. It also draws on the microfilm and physical collections of Russian newspapers at the National Library of Finland. The article shows how the murder activated the telegram network and initiated a series of news waves. The routes the Bobrikov news travelled, their tempo and the evolution of related stories tell a story of a networked but biased global news scene. In that scene, technological, commercial and cultural factors simultaneously facilitated and controlled what stories reached which papers and how.